Surviving mechanisms of power in immigration strategies: embracing Otherness and pluralisms. (June 2015) - Marino, Sara
The recent waves of immigration towards Europe are questioning our capacity to embrace Otherness, despite the well-acclaimed multiculturalism and hybridisation upon which Western societies have been built. Tension is building fast along the perceived 'explosion' of borders, and many immigrants are excluded from civic and political participation through discrimination, racism and xenophobia. The marginal positions of such minorities render them easily identifiable as scapegoats, susceptible to blame for problems that are, in fact, domestic. This article will investigate the mechanisms of power that still inform and redirect our immigration policies by looking at how the idea of 'Otherness' is embraced and understood. Desired outcomes include the opportunity to critically debate the relationship between citizenship and multiculturalism from a transnational perspective that privileges the practices of hybridisation and permeability against the ethnically oriented preservation of cultures.